2022
DOI: 10.3390/genes13020283
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome–Metabolome Analysis and Evaluation of the Dark_Pur Gene from Brassica juncea that Controls the Differential Regulation of Anthocyanins in Brassica rapa

Abstract: Chinese cabbage (Brassica rapa) is a major vegetable crop in China. The accumulation of anthocyanins improves the quality and flavor of Brassica crops and is beneficial for human health. There has been great research interest in breeding purple Chinese cabbage, for which it is necessary to study the key genes and mechanisms of anthocyanin accumulation. Through distant hybridization between purple mustard (Brassica. juncea) and green Chinese cabbage (B. rapa), purple Chinese cabbage plants were obtained. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…The BjPur gene in B. juncea was also mapped, and it encoded a new R2R3-MYB transcription factor [11], while the Dark_Pur gene and the BjPur gene were the same. The transformed purple Chinese cabbage plant was obtained via the particle bombardment of isolated microspores from Chinese cabbage to transform the Dark_Pur gene, thus verifying the function of the Dark_Pur gene [38]. In this study, the candidate interval was not further narrowed with more markers, and we hypothesized that the candidate gene regulating purple in pak choi may be the Dark_Pur gene from B. juncea.…”
Section: Fine Mapping and Candidate Gene Excavation For The Purple-le...mentioning
confidence: 74%
See 2 more Smart Citations
“…The BjPur gene in B. juncea was also mapped, and it encoded a new R2R3-MYB transcription factor [11], while the Dark_Pur gene and the BjPur gene were the same. The transformed purple Chinese cabbage plant was obtained via the particle bombardment of isolated microspores from Chinese cabbage to transform the Dark_Pur gene, thus verifying the function of the Dark_Pur gene [38]. In this study, the candidate interval was not further narrowed with more markers, and we hypothesized that the candidate gene regulating purple in pak choi may be the Dark_Pur gene from B. juncea.…”
Section: Fine Mapping and Candidate Gene Excavation For The Purple-le...mentioning
confidence: 74%
“…According to their phenotypes and genotypes, the target genes were initially located in the 30,067,746-31,915,855 bp region on chromosome A03 (Figure 3). In our previous study, a new purple B. rapa variety was obtained via distant hybridization from green B. rapa × purple B. juncea, and the purple-leaf-regulating gene Dark_Pur was mapped, which encoded the transcription factor R2R3-MYB from B05 in B. juncea [31,38]. The BjPur gene in B. juncea was also mapped, and it encoded a new R2R3-MYB transcription factor [11], while the Dark_Pur gene and the BjPur gene were the same.…”
Section: Fine Mapping and Candidate Gene Excavation For The Purple-le...mentioning
confidence: 99%
See 1 more Smart Citation
“…The vector pHSE401-mCherry contained the red fluorescence label promoted by mCherry and was a CRISPR/Cas9 vector. The pCAMBIA2300 vector contained the insert section of the Dark_Pur gene, with the CaMV35S promoter, eGFP, and Kan labels [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Delphinidin is formed by flavonoid 3'-5' hydroxylase (F3'-5'H), ANS, DFR, and UFGT in the third branching pathway. Liu Y et al [13] conducted an investigation on the structural genes of purple Chinese cabbage (Brassica rapa). Their study revealed significant up-regulation of key genes including PAL, C4H, 4CL, CHS, CHI, F3H, F3'H, FLS, DFR, and ANS across all three growth stages (cotyledon, seedling, and large-leaf stages).…”
Section: Introductionmentioning
confidence: 99%